Phytochemical Analysis and Detection of some Bioactive Compound in moringa oleifera Extract - Al Qrimli, Ayah F.; messer, Yousif Hussein; Hussein, Mohammed Nasser; Taghi, Zahraa Abass; Jaber, Zahraa Mohammed; Hussein, Mohammed (Journal of Pharmacology and Drug Development, 2024)
Moringa is a natural and cultivated variety of the genus Moringa of the family Moringaceae. The cultivation of Moringa is widespread due to multiple medicinal and healing properties. It is one of the richest plant sources of Vitamins A, B , C, D, E, K , in addition to proteins and minerals .The recent study aimed to phytochemically analyze Moringa oleifera grown in Iraqi environment and detection of some active compounds of the plant. Research reported that Moringa can support a healthy cardiovascular system, promote normal blood glucose levels, neutralize free radicals, provide excellent support of the body's anti inflammatory mechanisms, enrich anemic blood and support immune system. Moringa oleifera contains various phytoconstituents which contribute to its therapeutic uses such as alkaloids, saponins, tannins, steroids, phenolic acids, glycosides, flavonoids, and terpenoids. This study was able to identify the different phytochemical compounds present in Moringa cultivated in Iraq using preliminary chemical tests and to identify the presence of Quercetin using high performance liquid chromatography (HPLC) and thin layer chromatography (TLC). The chromatographic techniques proved the presence of Quercetin by showing identical retention time and retention factor almost identical to that produced by quercetin standard.